2006
DOI: 10.1080/10942910600596514
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Monitoring of Ripeness in Mango Cultivars by Acoustic Resonance Spectroscopy

Abstract: Mango cultivars, i.e. Neelam, Alphonso, Banganapalli, Totapuri, and Mallige were subjected to acoustic resonance spectroscopy at unripe, semi-ripe, and ripe stages, as well as in case of ripe bruised fruits. The Neelam variety of mango was screened for internal infestation by means of acoustic spectroscopy. Acoustic data on dominant and first frequencies, damping ratio, and firmness indices were obtained and correlated with mechanical penetration tests as well as a/b values of the tristimulus color profile. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Similar results were found in different mango cultivars during fruit ripening. [23] Chok Anan had a significantly higher firmness value than Nam Dok Mai at all ripening stages except the ripe stage (P ≤ 0.05). In addition, Jarimopas and Kitthawee [24] also found that the Chok Anan cultivar was firmer than the Nam Dok Mai throughout the development period.…”
Section: Mango Ripening Characteristicmentioning
confidence: 84%
“…Similar results were found in different mango cultivars during fruit ripening. [23] Chok Anan had a significantly higher firmness value than Nam Dok Mai at all ripening stages except the ripe stage (P ≤ 0.05). In addition, Jarimopas and Kitthawee [24] also found that the Chok Anan cultivar was firmer than the Nam Dok Mai throughout the development period.…”
Section: Mango Ripening Characteristicmentioning
confidence: 84%
“…Raju et al [6] have conducted studies on nondestructive monitoring of ripeness in different varieties of mangoes by acoustic resonance spectroscopy for online sorting of fruits. According to Vivek Venkatesh et al, [7] the maturity of fruits for a particular fruit variety can be estimated based on mass and volume, as they are indirectly correlated to the density of the fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Raju et al . (2006) reported a good correlation (correlation coefficients from 0.81 to 0.93) between the mechanical properties of mango fruit from five cultivars at four stages of ripeness and acoustic parameters. In citrus fruit, the acoustic impulse response was found be a good indication of firmness change (Wang et al ., 2006).…”
Section: Introductionmentioning
confidence: 95%